Dampak Komunikasi dan Budaya Organisasi Terhadap Kinerja Karyawan - Mei Habibah Dalimunthe; Rifka Fachrina; Suhairi Suhairi (Institut Agama Islam Nasional Laa Roiba Bogor, 2021)
The purpose of this article is to find out what and how much influence communication and organizational culture have on employee performance. In the business world, there are many opinions that say that communication has a significant effect on the development of the company, because in a company there is definitely a need for communication between employees and company owners or in other words between subordinates and superiors as well as what is called organizational culture. This is no less important than communication, where we can see that the impact is very large on the development or progress of a company. In addition, performance is also a set of measures of how well a job can be done when compared to the assessment standards that have been set and adjusted based on the results of the conclusions above, we can see that there is a significant communication effect or impact on the performance of employees.